Gen-Z Muslims and Interfaith Interaction: An Exploratory Study Among Youth in Rante Besi Village, Dairi - Mia Sari Tinambunan (Sufiya Journal of Islamic Studies, 2023)
This research aims to explore social interactions among Gen-Z teenagers in Rante Besi Village, Gunung Sitember Sub-district, Dairi Regency. The method used in this research is a case study with a qualitative approach. Primary data was obtained from interviews with a number of religious leaders, teenagers, and the local community, while secondary data was collected through literature review. The results show that social interactions between teenagers, especially those involving friends from different religious backgrounds, have an influence on the understanding and practice of religion among teenagers. The implication of this finding is the need for families and schools to play a more active role in providing attention and support for the practice of religion among adolescents, as well as creating space for strengthening spiritual values.